SEJARAH PROSA IMAGINATIF (NOVEL) ARAB; DARI KLASIK HINGGA KONTEMPORER - Kamil, Sukron (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2008)
Though the tradition of classic Arab was not prose, the Arabic fiction prose has developed since the end of Umayya Dinasty. The factors contributing to this development are the Qur’an that contains many stories and translation of fiction from Persian. Started from folklore and then translation, the Arabic fiction developed rapidly, followed by the publishing of short novels. Furthermore, there was a kind of fiction called maqamat.  The Arabic fiction developed in the classic period in the East of Arab was romantic fiction, while at the West part of Arab the development of classical fiction was marked by the works of romantic fictions by Ibn Al-Syahid and philosophical romantic fiction by Ibn Thufail. In modern era Arabic fiction was characterized with the translated works of Al Thanthawi. Then it was developed further by Al-Manfaluthi, a poet of classic and romantic. Novel Zainab by Husein Haikal indicated the birth of modern novels, followed by Taufik Hakim. Thaha Husein also developed Arabic fiction works that are still read nowadays. However, through Najib Mahfudz’s various works ranging from historical romantic, realist, and philosophical symbolic, the Arabic fiction claimed the world’s acknowledgement. The most recent trend of Arabic fiction is that the metaphysical and inter-textual novels come into light.